In vitro and in vivo determinations of the Anti-GDNF family receptor alpha 1 antibody in mice by immunochemistry and RT-PCR - Azizi, Hossein; Niazi Tabar, Amirreza; Skutella, Thomas; Govahi, Mostafa (International journal of fertility & sterility, 2020)
Background: The glial cell-derived neurotrophic factor (GDNF) family plays essential roles in the maintenance,growth, regulatory and signalling pathways of spermatogonial stem cells (SSCs). In this study, we analysed the expressionof anti-GDNF family receptor alpha 1 antibody (GFRa1) by immunohistochemistry (IHC), immunocytochemistry(ICC), Fluidigm real-time polymerase chain reaction (RT-PCR) and flow cytometry analyses.Materials and Methods: In this experiment study, ICC, IHC, Fluidigm RT-PCR and flow cytometry were used toanalyse the expression of the germ cell marker GFRa1 in testis tissue and SSC culture.Results: IHC analysis showed that there were two groups of GFRa1 positive cells in the seminiferous tubules basedon their location and expression shape - a small round punctuated shape on the basal compartment donut shape anda C-shaped expression located between the basal and the luminal compartments of the seminiferous tubules. OCT4and PLZF positive cells may have similar patterns of expression as the first group. Assessment of the seminiferoustubule sections demonstrated that about 27% of the SSCs were positive for GFRa1. Fluidigm RT-PCR confirmed thesignificant expression (p <0.001) of GFRa1 in the SSCs compared to testicular stromal cells (TSCs). Flow cytometryanalysis demonstrated that about 75% of the isolated SSCs colonies were positive for GFRa1.Conclusion: The results indicated that GFRa1 had a specific expression pattern both In Vivo and In Vitro . This finding could be helpful for understanding the proliferation, maintenance and signalling pathways of SSCs, and differentiation of meiotic and haploid germ cells.